Towards curative therapy of chronic viral hepatitis = Kurative Therapien der chronischen Virushepatitis - Bartenschlager, Ralf; Urban, Stephan; Protzer-Knolle, Ulrike (Zeitschrift für Gastroenterologie, 2019)
Persistent infection with hepatitis viruses is a major medical burden that unfortunately is often ignored in the general public. This results in a massive under-diagnosis of these infections. According to the world health organization, the number of people dying every year from the consequence of hepatitis virus infection has surpassed the death rate caused by malaria and HIV and is equivalent to the one of tuberculosis. These numbers call for more intense efforts to devise more effective, ideally curative therapies that must become as widely accessible as they are e. g. for HIV infected individuals. A major step forward has been the development of curative antiviral therapy for chronic hepatitis C. In the case of hepatitis D virus, new drug candidates have been developed that should receive conditional approval very soon. For chronic hepatitis B, development is lagging behind but thanks to a re-emerging interest of pharmaceutical industry that was triggered by the success of hepatitis C therapy and the availability of novel infection systems, new attempts towards curative approaches for this highly prevalent infection are undertaken. Here we summarize the current status of therapy development for chronic viral hepatitis that ultimately aims at cure.
Gesehen am 24.07.2019